(untitled) (Itinera, 2022)
The main purpose of this research is to analyze and understand the use of artistic and non-artistic images between East and West and especially of images accompanied by words written in Arabic. In reality there is a lot of information, images and falsifying words, in fact as stated by the French philosopher Jean Baudrillard: "when the image cancels reality" it is our duty to interpret it and give it the right meaning (Jean Baudrillard, 1988). In this regard We can say with certainty that very often, when the images shown contain writings in Arabic or in other languages that are not well known in the West, the message may not be fully intelligible or decodable and this prevents the understanding of the images themselves which may mistakenly be deemed untrue. We live in the era of images, and since these dominate the panorama of the contemporary world at the level of science, culture, economy and media, today as never before they are so fundamental in political and social life. To better understand this phenomenon of dependence of individuals on technology, television, social networks and videos, we will use the methodology of interpretation that will allow us to analyze these phenomena and these means which, taken in themselves, have no negative or positive value, which however, they must be considered critically in order to be able to use them correctly and consciously. With this research I aim to establish a link between different cultures, to find a common thought and contribute to the formation of a society, united against violence and terrorism.